Attitudes Towards and Management of Opioid-induced Hyperalgesia: A Survey of Chronic Pain Practitioners. Issue 5 (May 2020) - Kum, Elena; Buckley, Norman; de Leon-Casasola, Oscar; Lema, Mark; Busse, Jason W.
Abstract : Objectives: Opioid-induced hyperalgesia (OIH) is a phenomenon whereby opioids increase patients' pain sensitivity, complicating their use in analgesia. We explored practitioners' attitudes towards, and knowledge concerning diagnosis, risk factors, and treatment of OIH. Materials and Methods: We administered an 18-item cross-sectional survey to 850 clinicians that managed chronic pain with opioid therapy. Results: The survey response rate was 37% (318/850). Most respondents (240/318, 76%) reported they had observed patients with OIH in their practice, of which 38% (84/222) reported OIH affected >5% of their chronic pain patients. The majority (133/222, 60%) indicated that OIH could result from any dose of opioid therapy. The most commonly endorsed chronic pain conditions associated with the development of OIH were fibromyalgia (109/216, 51%) and low back pain (91/216, 42%), while 42% (91/216) indicated that no individual chronic pain condition was associated with greater risk of OIH. The most commonly endorsed opioids associated with the development of OIH were oxycodone (94/216, 44%), fentanyl (86/216, 40%), and morphine (84/216, 39%); 27% (59/216) endorsed that no specific opioid was more likely to result in OIH. Respondents commonly managed OIH by opioid dose reduction (147/216, 68%), administering a nonopioid adjuvant (133/216, 62%), or discontinuing opioids (95/216, 44%). Discussion: Most clinicians agreed that OIH is a complication of opioid therapy, but were divided regarding the prevalence of OIH, etiological factors, and optimal management. Abstract : Supplemental Digital Content is available in the text.